Concomitant use of isavuconazole and CYP3A4/5 inducers: Where pharmacogenetics meets pharmacokinetics. Issue 9 (19th May 2021) - Van Daele, Ruth; Debaveye, Yves; Vos, Robin; Van Bleyenbergh, Pascal; Brüggemann, Roger J.; Dreesen, Erwin; Elkayal, Omar; Guchelaar, Henk‐Jan; Vermeersch, Pieter; Lagrou, Katrien; Spriet, Isabel
Abstract: Background: Isavuconazole is a triazole antifungal drug, approved for the treatment of invasive aspergillosis and mucormycosis. Isavuconazole is metabolised by CYP3A4 and CYP3A5, and it has been shown that the CYP3A inducer rifampin reduces isavuconazole exposure. By extrapolation, the concomitant use of isavuconazole with moderate and strong CYP450 inducers is contraindicated, although it is known that some CYP450 inducers are less potent in comparison with rifampin. Objectives: We aim to document exposure to isavuconazole in patients concomitantly treated with a CYP450 inducer that is less potent compared to rifampin. Moreover, although it is well known that CYP3A enzymes are important for the metabolism of isavuconazole, this induction effect has never been studied in combination with the patient's CYP3A genotype. Patients: We report three patients treated with both isavuconazole and a CYP3A inducer that is less potent compared to rifampin (rifabutin or phenobarbital), in whom we determined isavuconazole concentrations. Results: These cases suggest that the CYP3A4/5 genotype is an important determinant for isavuconazole exposure and that it might also influence the CYP450 induction interaction. Conclusions: CYP3A inducers that are less potent compared to rifampin, may be combined with isavuconazole in patients with loss of CYP3A5 activity (CYP3A5*3/*3). Therapeutic drug monitoring is recommended during this combination. However, low‐isavuconazole exposure was observed in the extensive metaboliser with CYP3A4*1/*1 and CYP3A5*1/*3 alleles.